Fracture Criterion for Carbon Fiber Reinforced Polymer Sheet to Concrete Interface Subjected to Coupled Pull-Out and Push-Off Actions - Dai, Jian-Guo; Wan, Bao-Lin; Yokota, Hiroshi; Ueda, Tamon (Advances in Structural Engineering, 2009)
Flexural strengthening of reinforced concrete (RC) beams using externally bonded fiber reinforced polymer (FRP) sheet is a popular application nowadays. In this application, the FRP to concrete bond interface is typically exposed to a mixed-mode loading condition at the vicinity of a critical flexural/shear crack, which includes a pull-out action parallel to the interface and introduced by the opening displacement of the flexural/shear crack together with a push-off action perpendicular to the interface and introduced by the shear sliding displacement of the flexural/shear crack. This paper presents an experimental program to evaluate the fracture properties of the FRP to concrete interface under the coupled pull-out (mode II) and push-off (mode I) loading condition. An analytical model was developed to evaluate the mode I and mode II strain energy release rates and the corresponding fracture mechanisms of the FRP to concrete interface under a pure bending action, a pure dowel action, and the coupled action of both, respectively. The reliability of the proposed analytical model was verified in comparison with the experimental results.